PENGARUH FAKTOR KEUANGAN DAN NON KEUANGAN TERHADAP PEMBERIAN OPINI AUDIT GOING CONCERN OLEH AUDITOR - Ajeng Triyas Oktaviani; Zaky Machmuddah (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2019)
The purpose of this research is to find out the influence of profitability ratio, leverage ratio, company size, company growth, previous year’s audit opinion, and reputation of public accounting firm ongoing-concern audit opinion. A sampling of this research was obtained by purposive sampling method by focusing on manufacturing companies listed on the Indonesia Stock Exchange over the period 2014-2016, hence getting samples of 31 companies with the numbers of observations are 93 data. The method of data analysis of this research is the logistic regression. Based on the analysis result is known that profitability ratio and previous year’s audit opinion have an effect on going-concern audit opinion. While the ratio of leverage, company size, company growth, and public accounting firm’s reputation have no effect on the going-concern audit opinion.